El interés superior de la infancia considerada indígena (2018)
In modern constitutional systems, various international instruments have been planned and signed and a whole legal bloc has been established, which provides for specific rights for girls, boys and adolescents; which establishes the responsibility that all public and private authorities and institutions have for their well-being, categorized as a vulnerable social sector, the problem is aggravated by a new suspicious category of belonging to an ethnic group where the conditions of marginalization are accentuated , spaces that for a long time have been excluded from the legal debate, from public policies and that require an effective resizing. The present article, in its essay modality, aims to make some conceptual and legal clarifications, approach that is carried out as a dogmatic and normative study, referenced from the indigenous social legal environment in Oaxaca, Mexico.